Sistem Pakar Untuk mendiagnosis Gangguan Jiwa Schizophrenia - Landung Sudarmana; Febty Lestari (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Patients with mental illness (schizophrenia) are quite large. According to the results of Basic Health Research in 2015, there is 0.467 percent of the population in Indonesia, in other hands, 1.093.150 Indonesians were suffered from schizophrenia, if schizophrenia does not get attention and appropriate treatment, it will be very bad for the patient. Community stigma about mental disorder often leads schizophrenia patients to be too late taken to a health facility. People believed that schizophrenia is caused by mystical things so that the first treatment is brought the patients to alternative medications. The development of a very rapid computer nowadays makes us easily build a web-based expert system. This expert system is trying to find a satisfactory solution as an expert does. The system was developed to diagnose the schizophrenic mental disorder and the diagnosis was done by analyzing the inputs symptoms, in the form of checklists of what people were felt, then choosing the density of its severity. The results of the diagnosis provide an outcome, i.e. the names of the disease along with the possible percentage value generated based on the selected symptoms. This research intended to build an expert system using PHP and MySQL programming language to store its database, while the inference method using forward chaining is the process of tracing that begins by displaying a data set or convincing facts to the final conclusion. This research resulted a diagnosis schizophrenic mental disorder expert system that is capable to early diagnosing schizophrenic disorder, based on the symptoms that have been selected by the user with a simple appearance that is easy to understand and can be accessed by many users.